Faktor yang Berhubungan dengan Kejadian Anemia di Klinik Evie Kecamatan Babalan Kabupaten Langkat Provinsi Sumatera Utara Tahun 2024 - Damayanty S; Ade Rachmat Yudiyanto; Friza Novita Sari Situmorang; Sonia Oktavia Purba (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
Anemia in pregnant women is the main cause of bleeding and infection which is a major factor in maternal death. A woman who experiences bleeding after giving birth can suffer from severe blood deficiency (anemia) and experience long-term health problems. With a rate of 305 per 100,000 live births, Indonesia has a high maternal mortality rate (MMR) when compared to other ASEAN countries. The MMR target is 70 per 100,000 live births in 2030, in accordance with the Sustainable Development Goals (SDGs) (Sustainable Development Goals (SDGs), 2017; WHO, 2022). Currently, the rate of anemia in pregnant women is still high. Based on 2018 RISKESDAS data, the prevalence of anemia in pregnant women is 48.9%, meaning that 4-5 out of 10 pregnant women suffer from anemia. Maternal Mortality Rate (MMR) or Maternal Mortality Ratio (MMR) is an important indicator of the level of public health and is a sensitive indicator in describing the welfare of society in a country. . This research uses a cross-sectional strategy, using numerical data through a retrospective survey with a sample of 35 people. Research Results Based on the results of statistical tests, it was found that p.value = 0.003 and α = 0.05, where the P.value (0.003) < α (0.05) there is a relationship between maternal parity and the incidence of anemia. Based on the results of statistical tests, it was found that p.value = 0.005 and α = 0.05, where the P.value (0.005) < α (0.05), so it can be concluded that there is a relationship between maternal age and the incidence of anemia. Based on the results of statistical tests, it was found that p.value = 0.005 and α = 0.05, where the P.value (0.005) < α (0.05), so it can be concluded that there is a relationship between pregnancy spacing and the incidence of anemia. Based on the results of statistical tests, it was found that p.value = 0.005 and α = 0.05, where the value of P.value (0.005) < α (0.05), so it can be concluded that there is a SEZ status with anemia incidence